2023
DOI: 10.1002/pds.5654
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of ADHD medication use before, during, and after pregnancy: A population‐based study from Norway and Sweden

Abstract: PurposeTo describe ADHD medication use trajectories around pregnancy in Norway and Sweden.MethodsWe identified pregnancies resulting in births using linked data from birth and prescribed drug registers of Norway (2006–2019, N = 813 107) and Sweden (2007–2018, N = 1 269 146). We restricted to women who filled prescriptions for ADHD medication during pregnancy or in the year before or after. We described exposure as use versus no use, and total amount of drug dispensed in defined daily doses (DDDs). Group‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…We identified four similar trajectory patterns as a recent study of ADHD medication trajectories using Norwegian and Swedish register data [ 17 ]; however, the proportion of pregnancies classified in each of the trajectory patterns varied, with a notably higher proportion of continuers in Denmark. This may be partly driven by the specification of the models, which resulted in a more highly selected group defined as continuers in Norway and Sweden (5.7%), with a higher proportion of women using ADHD medication in each period (around 80–90%).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We identified four similar trajectory patterns as a recent study of ADHD medication trajectories using Norwegian and Swedish register data [ 17 ]; however, the proportion of pregnancies classified in each of the trajectory patterns varied, with a notably higher proportion of continuers in Denmark. This may be partly driven by the specification of the models, which resulted in a more highly selected group defined as continuers in Norway and Sweden (5.7%), with a higher proportion of women using ADHD medication in each period (around 80–90%).…”
Section: Discussionmentioning
confidence: 70%
“…It is essential to address this gap, as medication treatment decisions during these periods can have significant implications for both maternal and fetal/neonatal health. A recent study from Sweden and Norway found that ADHD medication use among women around pregnancy and postpartum follows multiple distinct patterns, with the majority discontinuing or pausing ADHD medication use around pregnancy, and continuation being rare [ 17 ]. These results need to be replicated to provide external validation.…”
Section: Introductionmentioning
confidence: 99%